Scale’s impact in education system’s performance: Cases in Draa-Tafilalet, Morocco - Mariam Akdim; Aboubakr Sabiri; Hamid Akdim; Sabah Selmaoui; Anouar Alami; Nadia Benjelloun; Moncef Zaki (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aimed to apprehend the scale’s role in education planning and performance. The national scale approaches tend to neglect local specificities. The relevance of the provincial and local scales is underlined in Draa-Tafilalet region (Morocco). By comparing the provincial data and indicators to study the education system's efficiency, we argue that these are pertinent scales to further understanding the needs, causality and key parameters of education. Collected data is analyzed using the data envelopment analysis (DEA). Useful indicators to compare the spatial variability of the education system’s efficiency were produced and discussed at a provincial scale and interpreted considering the local socioeconomic characteristics in each province. The five provinces of the region (Errachidia, Ouarzazate, Tineghir, Midelt, Zagora, and Midelt) are considered as adapted decision-making unit (DMU) in the study. The results show the provincial scale is relevant to apprehend the education system’s performance. It is also important in education planning. The spatial differences in education efficiency at this scale show evidence of weak education impacts among rural populations in the recently created provinces such as Tineghir, Midelt, and Zagora. The criterion of education efficiency measured by DEA ranks Tineghir in the last position. This province needs special attention in planning and development.